Adaptability and Productivity of Forage Crop under Hortipastoral System - Kundan Singh , Mukesh Singh , Atul Singh , Anuj Kumar Singh and A. K. Singh, (Indian Journal of Extension Education, 2016)
A survey was conducted in Faizabad district of eastern Uttar Pradesh, India was observed that farmers were cultivatingcomprehensively fodder crop with horticulture crop to bridge the huge gap between demand and supply of quality feedand forage required to be narrowed down. Research and development efforts made so far indicated that agroforestryplayed an important role in augmenting the supply of fodders especially in sodic land of eastern Uttar Pradesh, which isestimated to be one third of total area, reported. In order to raise the productivity of forage in more area of sodic land is tobe brought under agroforestry and also cost effective technology is required to be developed. Adaptation of the foragecropping pattern in these area is very high because the soil structures is not suitable to propagate cash crop. In agro forestrysystems farmers are using the intra spacing of the horticulture trees as under the canopy moisture and shade originate issuitable for growth and survival of forage crop during summer period. Out of 100 farmers reviewed, Mangifera indica+Zea mays +Dicanthium annulatum based horticulture system was adopted by majority of farmers in the study area.